ANALISIS PENANAMAN NILAI KARAKTER PADA MATA PELAJARAN PENDIDIKAN JASMANI DI SD NEGERI GUGUS 8 KECAMATAN PRAYA BARAT - Ali Aksa Rahman; Safruddin Safruddin; Husniati Husniati (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2021)
This study aims to describe how to instill character values ​​in physical education subjects at SD Negeri Gugus 8, Praya Barat District. The problems studied in this study are (1) what are the ways or steps in inculcating character values ​​in physical education subjects in elementary schools, (2) what are the things that affect the inculcation of character values ​​in physical education subjects. The type of research used is descriptive qualitative research with data collection techniques using interviews and documentation studies. While the data analysis technique used is the Miles and Huberman model which consists of stages (1) data reduction (2) data presentation (3) data verification, and using triangulation methods as data validity. Based on the results of data analysis, the results of the study indicate that, (1) there are several ways or steps that can be taken in instilling character values ​​in physical education subjects, namely: (a) teachers improve their attitudes first (b) familiarize students with praying before and after learning; (c) familiarize students with rows; (d) maximizing each set of learning practices; (e) modification of game rules on learning materials; (f) reaffirming the character values ​​contained in the learning materials at the learning reflection stage; (g) coordinate with parents and guardians of students. (2) things that affect the inculcation of character values ​​in physical education subjects consist of: (a) inhibiting factors which include certain cultural traditions in society, limitations of tools and media, and student delinquency; (b) supporting factors, which include teachers, student readiness, learning methods and techniques, as well as the involvement of various parties.